"Banks of the People": The Life and Death of the U.S. Postal Savings System. Issue 1 (9th September 2017) - Shaw, Christopher W
Abstract: From 1911 to 1966, the United States government operated a savings bank at local post offices. Throughout the early 20th century grassroots agitation to expand the Postal Savings System served as an oppositional political force to the power of bankers. Working people advocated a postal bank that would prioritize financial security, affordable credit, and macroeconomic stability. The banking fraternity aggressively opposed efforts that workers and farmers made to expand postal savings. The failure of more than one-fifth of the nation's banks during the early Great Depression placed the private banking system's future survival in doubt. The extension of postal savings was a distinct possibility. However, New Deal programs responded to the banking crisis by guaranteeing bank deposits and providing affordable credit to homeowners and farmers. These reforms reduced popular interest in extending postal savings. By 1966 the political opposition facing banking interests was much diminished. Bankers finally succeeded in terminating the Postal Savings System.